Variability of the Canary Current Diagnosed by Inverse Box Models - Casanova Masjoan, Maria; Pérez Hernández, María Dolores; Vélez Belchí,Pedro; Cana, L.; Hernández-Guerra, A. (Journal of Geophysical Research: Oceans, 2020)
Four hydrographic cruises carried out between ~26.5 and 31°N in the eastern North Atlantic Subtropical Gyre in fall (2016 and 2017) and spring (2017 and 2018) are used to identify water masses and infer oceanic circulation. Geostrophic velocities are initially adjusted by referencing them to data from a Lower Acoustic Doppler Current Profiler (LADCP) and later to velocities estimated with an inverse box model. The distribution of the intermediate water masses (700 to 1,400 m depth) varies seasonally. Antarctic Intermediate Water (AAIW) comprises the largest contributor to the seasonal cycle in the intermediate water masses. Circulation of the Canary Current (CC) differs in fall and spring. In fall, the CC flows southward through the western islands and recirculates south of the archipelago, subsequently flowing northward through the passage between the eastern islands and Africa. North of Lanzarote, the recirculated CC intensified as it is joined by a southeasterly branch of the CC north of Lanzarote. In spring, the net transport of the CC is southward. High interannual variability in mass transport is evident in both spring and fall as a result of the position of the current, with its easternmost (westernmost) position found in spring (fall) 2018 (2016). At intermediate levels, highly variable northward/southward transport is apparent in fall over the African slope, with the Intermediate Poleward Under Current (IPUC) only present in 2017. 3,405 Q1